From School to Industry : The Relevance of Vocational School Competencies in Machining Technology to Manufacturing Industry Needs - Zhahara, Zhahrotul; Solehudin, Agus; Berman, Ega Taqwali (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze the relevance of technical machining skills competencies at SMK Negeri 1 Karawang to labor needs in the manufacturing industry sector. The research method used is a survey with a quantitative approach. The research instrument is a questionnaire given to 68 students in the 12th grade of the technical machining program. The data analysis technique used was descriptive statistical analysis, calculating the percentage of respondents' answers based on the Likert scale to evaluate the alignment of the curriculum and graduates' competencies with industry demands. The research results indicate that the competencies possessed by graduates of SMK Negeri 1 Karawang are highly relevant and aligned with the demands of the job market. This is evident from the curriculum content alignment rate, which reached 85%. Specifically, graduates' competencies in cognitive aspects achieved a percentage of 86%, while psychomotor aspects also scored 86%. Meanwhile, the affective aspect received the highest score at 88%. However, there are still shortcomings in the mastery of soft skills, such as the 5S principles (commonly understood as Sort, Set in order, Shine, Standardize, and Sustain, though adapted here for workplace politeness and courtesy as Smile, Greeting, Politeness, and other relevant workplace behaviors might be more contextually defined) and 5P (Precision, Productivity, Maintenance, Prevention, and Improvement), as well as workplace safety culture (Safety) and work ethics. These findings recommend strengthening soft skills in the curriculum, enhancing collaboration between schools and industry, and conducting regular curriculum evaluations to ensure that graduates' competencies remain aligned with the needs of the job market.